The Gendered Intergenerational Transmission of Managerial Status - Martindale, Nicholas; Lyttelton, Thomas; Henriksen, Lasse Folke (American Sociological Review, 2026)
Prior research on managerial attainment highlights inequalities based on gender and ethnicity, but the role of social origins has been neglected. Moreover, past research on intergenerational social mobility does not focus specifically on how parents’ and children’s occupations may be linked. We develop a theoretical model of intergenerational managerial status transmission that we test using event history analysis that tracks managerial attainment (2000 to 2019) for over half a million Danish workers (born 1965 to 1975). Results reveal that children of managers are substantially more likely to become managers than the children of non-managers, and this inheritance is stronger for sons and for those with senior managerial origins. For children of lower-level managers, this is primarily related to advantages in early life (parental economic capital, educational attainment), but descendants of senior managers additionally benefit from advantages that accumulate later (career trajectories, elite social connections). Gender and seniority effects intersect to produce a particularly striking advantage for the sons of senior-managerial fathers. Much of this advantage remains unexplained after testing a large set of potential mediators, implying a considerable role for male-dominated forms of elite cultural and social capital (e.g., membership in exclusive clubs) and underscoring the limits to formal organizational approaches to equalizing outcomes at the very top of the occupational hierarchy.